The Concept of National Defense in the Book Al–Difa’ ‘An Al-Wathan Min Ahammi Al-Wâjibâti ‘Alâ Kulli Wâhidin Minnâ by Agus HM. Sa’id Ridwan - Ela Agustina; Dewi Evi Anita (Pascasarjana Universitas Wahid hasyim Semarang, 2025)
This article examines how the principles of Nahdlatul Ulamaa are linked to the spirit of nationalism by analyzing the concept of defending the country, such as the jargon presented by KH. Hasyim Asy'ari said hubbul wathan minal iman, which means love of the homeland is part of faith. In a book entitled Al-Difa' An Al-Wathan Min Ahammi Al- Wâjibâti 'Alâ Kulli Wâhidin Minnâ (Defending the Motherland: Some of the Obligations of Every Individual) by Agus HM. Sa'id Ridwan also explained very clearly the forms and manifestations of defending the country as a reflection of love for Indonesia's homeland. This book discusses the importance of love for one's country and how important it is for Muslims to defend their country.Keyword: Defending, Motherland